Visualizing enteric nervous system activity through dye-free dynamic full-field optical coherence tomography - Durand, Tony; Paul-Gilloteaux, Perrine; Gora, Michalina; Laboudie, Lara; Coron, Emmanuel; Neveu, Isabelle; Neunlist, Michel; Naveilhan, Philippe (Communications biology, 2023)
Major advances have been achieved in imaging technologies but most methodological approaches currently used to study the enteric neuronal functions rely on exogenous contrast dyes that can interfere with cellular functions or survival. In the present paper, we investigated whether full-field optical coherence tomography (FFOCT), could be used to visualize and analyze the cells of the enteric nervous system. Experimental work on whole-mount preparations of unfixed mouse colons showed that FFOCT enables the visualization of the myenteric plexus network whereas dynamic FFOCT enables to visualize and identify in situ individual cells in the myenteric ganglia. Analyzes also showed that dynamic FFOCT signal could be modified by external stimuli such veratridine or changes in osmolarity. These data suggest that dynamic FFOCT could be of great interest to detect changes in the functions of enteric neurons and glia in normal and disease conditions. Full-field optical coherence tomography (FFOCT) can be used for the visualization of the myenteric plexus network and individual myenteric ganglia cells in situ, showing that FFOCT is a suitable method to image enteric nervous system activity.